Pengaruh Pelatihan Perawatan Genitalia Vulva Hygiene Untuk Pencegahan Kegawatdaruratan Kesehatan Reproduksi Pada Wanita Dewasa - Huwaina Af’idah; Nina Fentiana Daud; Muchti Yuda Pratama (Universitas Pahlawan Tuanku Tambusai, 2026)
Female genital care is also known as vulva hygiene. Genital care (vulva hygiene) training for women aims to provide knowledge and skills in maintaining genital hygiene to prevent infection, maintain reproductive health, improve physical and psychological comfort, and prevent reproductive health emergencies in women. This study aims to analyze the effect of genital care training on adult women's skills in preventing reproductive health emergencies using a simulation/demonstration method of genital care (vulva hygiene). This study was a quantitative study using a one-group pretest-posttest design with a sample size of 40 adult women using a purposive sampling approach. Data were analyzed using a T-test. The results of this study showed a significant difference in skill levels between the pre- and post-simulation groups (p<0.005). Therefore, it is concluded that genital care (vulva hygiene) training using direct simulation can improve the ability to prevent reproductive health emergencies. Therefore, training using this simulation method is expected to be used for various types of learning activities: cognitive, affective, psychomotor, and interpersonal. Keywords: Training, Care, Genitalia, Vulva, Hygiene, Emergency, Health, Reproduction, Women